Wind-induced mechanical rupture of birch pollen: Potential implications for allergen dispersal. (November 2015) - Visez, Nicolas; Chassard, Guillaume; Azarkan, Najiha; Naas, Oumsaad; Sénéchal, Hélène; Sutra, Jean-Pierre; Poncet, Pascal; Choël, Marie
Abstract: Mechanical rupture of pollen grains after a mechanical shock against a solid surface was tested as a new approach to one of the mechanisms related to the release of allergen loaded particles from pollen. Birch pollen was aerosolized and sent into an impactor to mimic a shock against a surface (trees, soil, walls, etc.) at wind speeds of atmospheric-relevance. Small particles in the range of 1–2.5 µm were released subsequently to pollen impaction. The number of particles released increased with the velocity of impaction and with the water content of pollen. Damaged grains were observed by transmission electron microscopy and released particles are most likely cytoplasmic granules. This mechanism of pollen rupture and/or discharge may be of great importance in urban environment and may significantly contribute to thunderstorm-related allergic asthma and other associated pollen subparticles IgE mediated diseases. Graphical abstract: Highlights: Pollen rupture was induced after a mechanical shock. Released particles were in the 1–2.5 µm range. Higher wind velocities increased the extend of pollen rupture. Increase in pollen water content also increased the number of grains ruptured.